1995
DOI: 10.1111/j.1365-2893.1995.tb00036.x
|View full text |Cite
|
Sign up to set email alerts
|

Interferon‐α2a for chronic hepatitis B with e antigen or antibody: comparable antiviral effects on wild‐type virus and precore mutant

Abstract: Recombinant interferon-alpha 2a (IFN-alpha 2a) in a total dose of 702 MU was given to 31 patients: nine with wild-type hepatitis B virus (HBV) and hepatitis B e antigen (HBeAg) (A); four with HBeAg and a mixed infection with wild-type HB and precore mutants (B); 11 with antibody to HBeAg (HBeAb) and a mixed infection (C); and seven with HBeAb and precore mutants alone (D). HBV DNA was not cleared in any patient in groups A and B. By contrast, in patients with HBeAb, HBV DNA was ultimately lost in four patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…Most studies have shown that approximately 30–40% of HBeAg-positive patients respond to IFN-α therapy. However, the rate to IFN-α therapy for HBeAg-negative patients is divergent: some studies reported that IFN-α response rate is up to 50% 4446 , whereas others showed long-term IFN-α response rate is less than 10% 4750 . Thus, we could not neglect the roles of other viral proteins, including HBsAg and HBp 23, 51, 52 , in the regulation of IFN-α actions.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies have shown that approximately 30–40% of HBeAg-positive patients respond to IFN-α therapy. However, the rate to IFN-α therapy for HBeAg-negative patients is divergent: some studies reported that IFN-α response rate is up to 50% 4446 , whereas others showed long-term IFN-α response rate is less than 10% 4750 . Thus, we could not neglect the roles of other viral proteins, including HBsAg and HBp 23, 51, 52 , in the regulation of IFN-α actions.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies so far have shown poor long-term response rates of even less than 10% in HBeAg-negative hepatitis, [5][6][7][8][9] but some studies reported response rates up to 50%. [10][11][12] The highly divergent response rates to IFN therapy for HBeAg-negative hepatitis are difficult to explain. In HBeAg-positive hepatitis low HBV-DNA titers predict a favorable response to IFN.…”
Section: Discussionmentioning
confidence: 99%
“…However, the results are controversial. [10][11][12]18,19 Mutations in the polymerase gene play an important role for resistance to nucleoside analogues, but do not seem to have an effect on the outcome of IFN therapy. Whether variations of the core gene affect the response to IFN is under discussion.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The G1896A stop codon mutation in the precore region was detected by an enzyme-linked minisequence assay (Smitest HBV Pre-C ELMA, Roche Diagnostics). 9,10 When the mutation rate was 0%, the results were recorded as wild type; otherwise, they were mutantpositive. The A1762T and G1764A double mutations in the CP region were detected by an enzyme-linked specifi c probe assay (Smitest HBV core promoter mutation detection kit, Genome Science Laboratory, Tokyo, Japan).…”
Section: Laboratory Assaysmentioning
confidence: 99%